Stormblade - Berberick, Nancy Varian (New York TSR, 1988)
Deep in the cavern kingdom of Thorbardin, the powerful Stormblade is secretly crafted by an elderly dwarf-master. A Kingsword, it is intended to break the deadlock among the ruling council of Thanes. When Stormblade is stolen and turns up years later, a series of exciting and deadly events are set in motion. Only a heroic dwarf knows the magic of the legendary blade, and he sets out to recover the lost weapon. To do so, he must travel to a land rife with war and treachery.
Include Illustrations
Keywords: Fantasy fiction, American -- Fantasy fiction